Integrating Tobacco Prevention Skills into an Evidence-Based Intervention for Adolescents with ADHD: Results from a Pilot Efficacy Randomized Controlled Trial - Corona, Rosalie (J Abnorm Child Psychol, 2020)
Adolescents with attention-deficit/hyperactivity disorder (ADHD) are at high risk for tobacco use, but tobacco use prevention strategies are not regularly incorporated into evidence-based ADHD interventions. We conducted a pilot randomized-controlled trial to determine the feasibility of integrating tobacco use prevention skills into a behavioral treatment for ADHD and to provide preliminary efficacy data comparing a combined (ADHD + tobacco) intervention (N = 40) to an ADHD only intervention (N = 23) on tobacco risk outcomes. Sixty-three adolescents (72% male; 13–17 years) with ADHD and their caregivers were randomly assigned to condition and families were masked to condition. Parent and adolescent ratings were collected at baseline, immediate post-intervention, and at 3- and 9-month follow-up assessments. The combined intervention was (1) implemented with high fidelity (94%), (2) well received by parents and adolescents as evidenced by high levels of treatment attendance (82%) and satisfaction with the intervention, and (3) associated with parent- and adolescent-reported reductions in tobacco use risk. Relative to the ADHD intervention, the combined intervention buffered against increases in tobacco risk, including reduced intentions to smoke and maladaptive social normative beliefs, and increased parental control, family cohesion, and family communication about substance use. Effect sizes at post-treatment were in the small to moderate range. Overall, this study provides preliminary support for a parent-adolescent behavioral treatment supplemented with family-based tobacco prevention strategies. This approach targets families already in treatment for ADHD, reducing barriers that occur when families attend multi-session prevention programs in addition to ADHD treatment.